Redefining Jihad, Hijrah, and Caliph in Mohja Kahf’s The Girl in the Tangerine Scarf - Djohar, Hasnul Insani; Oktaviano, Willy (Sunan Kalijaga State Islamic University & The Asia Foundation, 2024)
Abstract Historically, Orientalism has perceived Islam in reductionist views for centuries. To resist this basic view, it is crucial to investigate Mohja Kahf’s The Girl in the Tangerine Scarf (2005), which redefines Islam and Islamic terms, such as Jihad, Hijrah, and Caliph in more positive insights. Kahf’s text questions orientalists, which tend to misrepresent Muslims in a limited way, such as Jihad associated with terrorism and killing others instead of fighting against worldly desires. To contest these negative misrepresentations of the Muslim world, in her novel, Kahf uses Islamic sacred texts, such as Surah At-Taubah (Repentance) and Al-A’raf (The Heights), to redefine Islam as a religion, which promotes Salam (peace) and tolerance in the world instead of violence as misrepresented in Western liberalism. By engaging with postcolonial and Islamic studies, this paper investigates how Kahf uses the Quran and hadiths in her novel to reject imperialist perspectives. Thus, Kahf’s novel explores the Islamic sacred texts to inspire people how to live in a modern society by appreciating different people regardless of their different races and faiths and practicing tolerance to establish a more global civilized society. Keyword: US-Muslimah’s fiction, Quran and Hadiths, Jihad , Hijrah, Caliph and leader, Tolerance [Secara historis, Orientalisme telah memandang Islam dalam pandangan reduksionis selama berabad-abad. Untuk menolak pandangan dasar ini, penting untuk menyelidiki The Girl in the Tangerine Scarf (2005) karya Mohja Kahf, yang mendefinisikan ulang Islam dan istilah-istilah Islam, seperti Jihad, Hijrah, dan Khalifah dalam wawasan yang lebih positif. Teks Kahfi mempertanyakan para orientalis yang cenderung memberikan gambaran keliru tentang umat Islam secara terbatas, seperti Jihad yang dikaitkan dengan terorisme dan membunuh orang lain alih-alih berperang melawan keinginan duniawi. Untuk melawan kesalahpahaman negatif tentang dunia Muslim, dalam novelnya, Kahfi menggunakan teks suci Islam, seperti Surah At-Taubah (Pertobatan) dan Al-A'raf (Ketinggian), untuk mendefinisikan kembali Islam sebagai agama yang mengedepankan Salam ( perdamaian) dan toleransi di dunia dibandingkan kekerasan seperti yang disalahartikan dalam liberalisme Barat. Dengan terlibat dalam studi pascakolonial dan Islam, makalah ini menyelidiki bagaimana Kahf menggunakan Al-Quran dan hadis dalam novelnya untuk menolak perspektif imperialis. Oleh karena itu, novel Kahfi mengeksplorasi kitab-kitab suci Islam untuk menginspirasi masyarakat bagaimana hidup dalam masyarakat modern dengan menghargai orang yang berbeda tanpa membedakan ras dan keyakinannya serta mengamalkan toleransi untuk mewujudkan masyarakat beradab yang lebih global. Kata Kunci: Fiksi AS-Muslimah, Quran and Hadits, Jihad, Hijrah, Khalifah, Tolerance.]